Woman in journalism - Finley, Emma (My University, 1897)
Introduction: Not many years ago there were in the popular mind, but three professions—law, theology and medicine, more recent thought however has added two more, teaching and journalism. The latter is included because the times demand that not only the pulpit and bar, but the journalists chair as well, shall be filled by men of education. The readers of Mr. Frederic Hudson’s entertaining history of journalism in the U.S. from 1690 to 1872 have learned, long since, what the modern newspaper is, how it originated and where it is tending. It is a common saying in England that America is governed by newspapers and this by way of sneer. But long ago Jefferson anticipated and met this reproach, when he said “I would rather live in a country with newspapers and without a government than to live in one with a government and without newspapers.” Nowadays it has been found easier to overthrow a government at Paris-Madrid, Mexico, or Rome, than to stop a well-managed newspaper. The steam press, the electric telegraph, the enormous development of commerce and industry in the last half century have gen newspapers a position and a responsibility but little understood even by those who have the most to do with them.
Citation: Finley, Emma. Woman in journalism. Senior thesis, Kansas State Agricultural College, 1897.
Morse Department of Special Collections
Keywords: Newspapers; United states; Women; Journalists; Theses; Manuscripts (documents)